Aplikasi Enkripsi Pesan E-Mail Menggunakan Hybrid Cryptosystem AES dan RSA - Artajaya, Gede Krisna Surya; Muliantara, Agus; Putra, I Gusti Ngurah Anom Cahyadi; Suhartana, I Ketut Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 13 No 2 (2024): JELIKU Volume 13 No 2, November 2024, 2025)
The security of communication via e-mail is increasingly important in today's digital era, where cyber attacks are increasing. These threats require the development of effective solutions to protect the confidentiality and integrity of information in e-mail. This study presents the development of an e-mail messaging application that employs a hybrid cryptosystem combining Advanced Encryption Standard (AES) and Rivest-Shamir-Adleman (RSA) algorithms. The aim is to improve the security of e-mail communications by utilizing the strengths of both symmetric and asymmetric encryption methods. AES is used for its efficiency in encrypting large amounts of data, while RSA ensures secure key exchange. The application tested with blackbox testing to verify its functionality and brute force testing to assess the encryption's robustness. The results show that the application successfully passed the blackbox testing, demonstrating that it functions as intended. The encryption results of the application are also excellent, as evidenced by brute force testing which shows that the encryption cannot be broken. This hybrid approach, by integrating AES and RSA, provides a practical solution for enhancing e-mail security.